Sino-American Relations since the End of Bipolar World - Staňková, Nikola; Maslowski, Nicolas, 1972-; Druláková, Radka, 1973-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The purpose of this thesis is to demonstrate that American policy is reactive to China's changing status in international relations and Sino-American relationship have gone through various phases since the end of bipolar world, but security remains the main component that shapes Sino-American relations until today. During the Cold War, the main aspect of the relationship was common security threat that diminished with the end of bipolar world. After that, economy became more important and China developed a comprehensive national power. However, with China's new power status in international relations came new realities in Sino-American relations driven by the security concerns again.
Vedoucí práce: Nicolas Maslowski
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses